Disiplin Kerja, Karakteristik Individu dan Pengaruhnya Terhadap Kinerja Pegawai - Simatupang, Sudung; Butarbutar, Novita; Candra, Vivi (Jurnal Manajemen, 2021)
The aim is to see the effect of work influence on employee performance, which represents employee performance, as well as work discipline and workers on employee performance. Which is the object of research at the Social Service for Women's Empowerment and Child Protection in Pematangsiantar City with 40 employees. The analysis used is the validity and reliability test, normality, coefficient of determination, simple and multiple equations, then partial test (t test) and simultaneous test (F test). The results of the study found that all variables of this study: work discipline, individual appraisal and performance were declared valid and reliable. To test for normal distribution that the value of the variable is stated as normal distribution, then the coefficient of determination shows that each independent variable contributes to the employee performance variable. The results of the equation carried out with simple regression show positive results and with multiple equations it is found that the greater the contribution of individual factors to employee performance than work discipline. Partial test (t test) found a positive and significant effect of work discipline on employee performance, as well as to assess individual performance. Simultaneous test (F test) that work discipline and people have a positive and significant effect on employee performance